중등도 이하 소아 근시에서 안경과 각막굴절교정렌즈 착용이 안축장 성장에 미치는 영향 비교 - 김태희(Tae Hee Kim), 김명훈(Myung Hun Kim), 곽주영(Joo Young Kwag), 최진석(Jin Seok Choi), 박규홍(Kyu Hong Pak), 이경욱(Kyeongwook Lee), 박태성(Taeseong Park), 정성근(Sung Kun Chung), 현주(Joo Hyun) (Daihan angwa haghoi jabji, 2018)
목적: 중등도 이하 소아 근시에서 안경과 각막굴절교정렌즈(orthokeratology lens, OK) 착용이 안축장 성장에 미치는 영향 및 관련인자를 알아보고자 하였다. 대상과 방법: 2013년부터 2015년까지 내원한 6세에서 13세 사이 -4.50디옵터 이하의 구면렌즈대응치를 가진 소아 100명을 대상으로 후향적으로 OK군(75안)과 안경군(64안) 간에 안축장 변화와 안축장과 관계된 인자들을 분석하였다. 결과: 안축장 변화는 1년째에 OK군이 0.24 ± 0.29 mm의 증가를, 안경군이 0.42 ± 0.20 mm의 증가를 보였으며, OK군에서 안경군에 비해 유의하게 안축장 성장이 억제되는 양상을 보였다(Mann-Whitney U test, p<0.05). OK군에서 처음 착용한 나이만이 안축장 변화와 음의 상관관계가 있는 것으로 나타났다(Pearson's correlation, r=-0.481, p<0.05). 안경군에서는 처음 착용한 나이가 안축장 변화와 음의 상관관계(Pearson's correlation, r=-0.462, p<0.05)를, 그 외에 현성굴절검사의 초기 구면렌즈대응치 및 초기 구면렌즈값, 난시값은 안축장 변화와 양의 상관관계를 보였다. 안축장 변화를 비교해 보았을 때 OK를 착용한 경우 6세 이상 9세 미만군(28안)에비해 9세 이상 13세 이하군(47안)에서 유의하게 안축장 성장이 더 억제되는 양상을 보였다(Mann-Whitney U test, p<0.05). 결론: OK 착용은 안경 착용에 비해 효과적으로 안축장의 성장을 억제할 수 있으며, 9세 이상 13세 이하의 소아에서도 효과적인 안축장 성장 억제가 가능하다. Purpose: To assess the effect on axial elongation and associated factors between spectacles and of orthokeratology lens (OK) wearing in children with mild to moderate myopia. Methods: A total of one hundred subjects, ranging in age from 6 to 13 years, and with mild to moderate myopia no more than -4.50 diopters in spherical equivalent, visited our clinic from 2013 to 2015. The OK group (75 eyes) and the spectacles group (64 eyes) were compared and analyzed on the axial elongation and associated factors. Results: In the OK group, axial length was elongated in 1 year period with a mean increase of 0.24 ± 0.29 mm. In spectacles group, axial length was elongated in 1 year period with a mean increase of 0.42 ± 0.20 mm. The statistically significant suppression of axial elongation was observed in OK group compared to the spectacles group (Mann-Whitney U test, p < 0.05). For OK group, the age of starting OK (Pearson's correlation, r = -0.481, p < 0.05) was the only influencing factor on axial elongation, which had negative correlation with axial elongation. In spectacles group, the age of starting spectacles had negative correlation with axial elongation (Pearson's correlation, r = -0.462, p < 0.05) and baseline spherical equivalent, spherical diopter, cylindrical diopter from manifest refraction had positive correlation with axial elongation. Comparison of axial elongation in orthokeratology lens group and spectacles group by age groups (6 to 9 years [28 eyes], 9 to 13 years [47 eyes]), 9 to 13 years of orthokeratology lens group had the stronger suppression of axial elongation (Mann-Whitney U test, p < 0.05). Conclusions: The OK effectively suppresses axial elongation compared to the spectacles. Although the patients are in age from 9 to 13 years, the axial elongation was effectively suppressed. KCI Citation Count: 0